PENGAJARAN PENCATATAN BUKU BESAR PERUSAHAAN JASA DI SMK STRADA 1 - Nur Adibah, Zahra Fiany; Rasyid, Rosmita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The evolution of time has brought significant changes to life, especially in the field of accounting. Accounting is not only about recording financial transactions but is also a crucial management tool providing valuable information to support managerial decision-making processes. A service company operates in the service industry, offering services rather than physical products. They provide a variety of services to customers without tangible results. The Teaching Assistance activities conducted at SMK Strada 1 took place over 10 sessions, starting from August 28, 2023, to September 26, 2023, with the aim of developing the author's soft skills and hard skills in teaching and understanding basic accounting. The implementation method of this Merdeka Belajar Kampus Merdeka activity included presenting conceptual material, discussing practice problems, and providing learning aids such as games. The author gained new experiences in carrying out tasks in the educational institution, which had not been done before. The opportunity allowed the author to conduct face-to-face/offline teaching to the 10th-grade students of SMK Strada 1, focusing on basic accounting, especially the General Ledger. Through this activity, the author successfully improved communication skills in the teaching-learning process, aiming to broaden the students' knowledge in the field of accounting.